2004
DOI: 10.1007/s00259-004-1569-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of gated SPECT in the analysis of regional wall motion of the interventricular septum after coronary artery bypass grafting

Abstract: Gated SPECT with perfusion tracers can reliably differentiate pseudo-paradoxical from true paradoxical septal motion in patients with previous CABG, and it may be the method of choice for evaluating left ventricular performance in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Wranne et al (5) suggested that the persistence or disappearance of ASM in the late postoperative period depends on factors such as recovery of right heart function with restoration of tricuspid annular motion, development of retrosternal adhesions, and development of left or right ventricular volume overload. This abnormal cardiac mobility may be related to sternotomy and pericardiotomy with anteromedial translation of the heart during systole (11). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wranne et al (5) suggested that the persistence or disappearance of ASM in the late postoperative period depends on factors such as recovery of right heart function with restoration of tricuspid annular motion, development of retrosternal adhesions, and development of left or right ventricular volume overload. This abnormal cardiac mobility may be related to sternotomy and pericardiotomy with anteromedial translation of the heart during systole (11). …”
Section: Discussionmentioning
confidence: 99%
“…Presence or absence of ASM on cine MRI was determined using qualitative visual and quantitative assessment, and the final diagnosis was made by consensus. Septal wall motion was expressed as endocardial inward movement (in millimeters) from the end-diastolic to the end-systolic phase on cine MRI (11). For qualitative analysis of the ASM, we calculated the average value of regional wall motion in the septal segments (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, gating appears mandatory to interpret the meaning of defects in myocardial perfusion imaging in patients with left bundle branch block. Similarly, Giubbini et al demonstrated that the combination of functional (in particular wall thickening) and perfusion data obtained from gated SPECT is very effective in order to interpret the meaning of septal wall motion abnormalities in patients submitted to coronary artery bypass grafting and to differentiate between pseudo-paradoxical wall motion caused by heart surgery and paradoxical wall motion in patients with prior anterior myocardial infarction [99].…”
Section: Regional Function and Perfusionmentioning
confidence: 99%
“…We used wall thickening values in the 20-segment model as an adjunct for asynergy assessment. After intervention, since CABG was included in 17% of cases, septal motion showed abnormality even with good wall thickening [18,19]. We therefore determined that the motion was improved after reperfusion if the percentage of wall thickening was improved to >32%.…”
Section: Analysis For Viability Assessmentmentioning
confidence: 99%
“…Even if some myocardial segments showed severe contractile dysfunction, left ventricular global and regional contractility may recover owing to viable segments. Non-invasive myocardial viability assessment thus has been considered important, and various approaches have been utilized including contractile functional reserve by echocardiography with inotropic stimulation, myocardial perfusion imaging with single-photon emission computed tomography (SPECT) and positron emission tomography with 18 F-fuluorodeoxyglucose (FDG) [1][2][3][4][5][6]. Although FDG may provide better diagnostic ability for detecting potentially reversible myocardial dysfunction, single-photon myocardial perfusion tracers continue to be one of the best convenient choices for clinical practice.…”
Section: Introductionmentioning
confidence: 99%